Investigating the effects of protein disulfide isomerase A4 on influenza virus replication in mice and rabbit hemorrhagic disease virus 3C-like protease in cell death - Wickramasingha Mudiyanselage, Luija Nathali W W (Kansas State University, 2024)
Influenza A virus (IAV) infection is one of the important viral infections with a wide host range including mammals and birds. Protein disulfide isomerases (PDIs) are a diverse family of proteins that act mainly as thiol-disulfide oxidoreductases and redox chaperones facilitating proper folding and rearrangement of proteins. We have previously reported that the knockdown of PDI1, PDIA3, or PDIA4 using siRNAs resulted in a substantial decrease in the replication of both influenza A and B viruses in cells. Therefore, we investigated the effect of PDIA4 on the replication of IAV in constitutive PDIA4-knockout (KO) and wild-type (WT) C57BL/6J mice and PDIA4 KO and WT A549 cells. We observed comparable survival rates and lung viral loads between KO and WT mice and lower virus titers in A549 KO cells compared to WT cells, which indicate that constitutive knockout of PDIA4 did not reduce viral replication in mice, which may be due to compensatory host pathways. Rabbit Hemorrhagic Disease Virus (RHDV) can cause a highly contagious and often fatal disease that mainly affects domestic and wild European rabbits (Oryctolagus cuniculus). RHDV 3C-like protease (3CLpro) processes most cleavage sites on the viral polyproteins to produce functional non-structural proteins and is crucial in viral replication. The 3CLpro and 3C proteases of some viruses have also been reported to play a role in host immunity and inducing apoptosis. Therefore, we investigated the effect of RHDV2 3CLpro in cytotoxicity and its mechanism, and the roles of the catalytic activity of 3CLpro in mediating cell death and cytokine production. Our results showed that the expression of active RHDV2 3CLpro in HEK293T cells led to a significant reduction in cell viability and increased cell death, compared to those of the inactive 3CLpro or the empty vector, via activation of caspase 3/7 activity. The active RHDV2 3CLpro increased IFN-beta and the gamma-activated sequence (GAS) elements promoter activity compared to the inactive 3CLpro or the empty vector. However, a significant increase in IFN-beta mRNA expression levels was not observed. These results indicate that RHDV2 3CLpro induces apoptosis by activating caspase 3/7 via the catalytic activity of 3CLpro. Additionally, it suggests that RHDV2 3CLpro may mitigate IFN-beta mRNA expression induced by cell death.
Keywords: Influenza A virus; Protein disulfide isomerases; Rabbit Hemorrhagic Disease Virus; 3C-like protease